Kebijakan redaksi media di Indonesia dalam pemberitaan haji tahun 2020 - Ida Nuraini Dewi Kodrat Ningsih; Narayana Mahendra Prastya (Islamic Communication Journal, 2020)
There was uncertainty in Hajj 2020 due to the Covid-19 pandemic. Before the Kingdom of Saudi Arabia's government announced the limitation of Hajj 2020, several countries including Indonesia has decided not to cancel the hajj trip. In dealing with uncertain information, the public needs valid information because uncertainty leads to speculations. In this situation, the media has a vital role in giving valid and verified information. This article aims to know how Indonesia media editorial policy in hajj 2020 news coverage. The editorial policy consists of the news theme, news sources, and news reporting technique. The data collection use interview with five informants from different media. The results before the official announcement, media deliver the news about the future of Hajj 2020 and the Indonesian government plan in dealing with the situation. After the official announcement both from Indonesia and Saudi Arabia gov’t, the media deliver information about the procedure to refund the hajj fee. News sources are the Ministry of Religion of the Republic of Indonesia, pilgrims, and travel agencies, and umrah. News reporting techniques use teleconference, citing information from authority's official websites, and citing news from other news agencies.